Low-expansion silicon-carbon negative electrode material and preparation method thereof
By modifying porous carbon to form a MOF structure and controlling the in-furnace pressure during carbon deposition, the cycle stability problem caused by floating silicon in silicon-carbon negative electrode material is solved, and efficient silicon deposition and conductivity improvement are achieved.
Patent Information
- Application Number
- CN202411848590.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-28
AI Technical Summary
During the preparation of silicon-carbon negative electrode material, floating silicon formed by deposition of silicon source gas on the porous carbon surface is prone to powder and peel off due to volume changes, resulting in a decrease in the circulation stability of the material.
By modifying porous carbon, a MOF structure with high specific surface area and excellent affinity adsorption of silicon source gas is formed, which reduces the formation of floating silicon, and controls the in-furnace pressure growth curve during carbon deposition to obtain a dense carbon coating layer inside and outside.
It effectively reduces the floating silicon content on the porous carbon surface, improves the cyclic stability of the negative electrode material, and improves the ion transport performance and improves the conductivity while maintaining the cyclic performance.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of negative electrode materials, and in particular to a low expansion silicon-carbon negative electrode material and a preparation method thereof. Background Art
[0002] Silicon-carbon negative electrode materials have attracted much attention due to their high theoretical specific capacity and have become one of the key materials for improving battery energy density. Such materials are usually composed of silicon and carbon composites, aiming to combine the high energy storage capacity of silicon with the good conductivity and structural stability of carbon materials. In particular, silicon-carbon negative electrode materials based on porous carbon not only provide abundant ion transport channels through their porous carbon framework, but also effectively limit the volume expansion of silicon particles during the charging and discharging process, thereby achieving high discharge capacity while significantly improving the cycle stability of the battery.
[0003] In the preparation process of the aforementioned silicon-carbon negative electrode material, a vapor deposition process is usually used to deposit silicon and carbon to obtain a silicon-carbon composite structure. For example, the invention application with publication number CN117776183A discloses a porous carbon and its preparation method, a silicon-carbon negative electrode material, and a method for preparing a silicon-carbon negative electrode material. First, silicon is deposited in the pores of the porous carbon, and the pore structure of the porous carbon is used to effectively limit the expansion of silicon. Then, carbon is deposited on the surface of the porous carbon to form a carbon coating layer to isolate the deposited silicon in the pores from direct contact with the electrolyte. This process has high deposition efficiency, and the resulting material has excellent electrical properties.
[0004] However, it is worth noting that during the silicon deposition process, the silicon source gas will not only be adsorbed by the pores and decomposed and deposited, but will also be adsorbed by the surface of the porous carbon and decomposed and deposited. This part of the silicon deposited on the surface of the porous carbon is very easy to pulverize and peel off due to volume changes during the charge and discharge process due to the lack of the confinement effect of the pores, thereby losing cycle stability. This phenomenon is called the "floating silicon" effect. The presence of floating silicon not only reduces the utilization rate of the material, but may also lead to the instability of the electrode structure, thereby affecting the overall performance of the battery. Summary of the invention
[0005] In order to optimize the deposition path of silicon, reduce floating silicon in silicon-carbon negative electrode materials, and improve the cycle stability of silicon-carbon negative electrode materials, the present application provides a low-expansion silicon-carbon negative electrode material and a preparation method thereof.
[0006] In a first aspect, the present application provides a low expansion silicon-carbon negative electrode material, which comprises modified porous carbon, nano-silicon deposited in the pores of the porous carbon, and a carbon coating layer located on the surface of the porous carbon; the porous carbon is prepared according to the following steps: The carbon source precursor is mixed with an alkaline activator and activated to obtain a porous carbon matrix; The porous carbon matrix and the zirconium salt are added into deionized water, ultrasonically dispersed, and then an organic ligand is added for coordination assembly to obtain a modified porous carbon; The mass ratio of the porous carbon matrix to the zirconium salt is 100:1.6-3.8.
[0007] Preferably, the mass ratio of the carbon source precursor to the alkaline activator is 1:1.5 to 3.5.
[0008] Preferably, the molar ratio of the organic ligand to the zirconium ion is 1:1.5-2.
[0009] Preferably, the zirconium salt is selected from zirconium nitrate or zirconium sulfate.
[0010] Preferably, the organic ligand is an amino-containing polycarboxylic acid ligand having an amino group and at least two carboxyl groups.
[0011] Exemplarily, the amino-containing polycarboxylic acid ligand is 2-aminoterephthalic acid or ethylenediaminetetraacetic acid.
[0012] Preferably, the specific surface area of the modified porous carbon is 1400 to 2400 m 2 / g.
[0013] Preferably, the particle size of the modified porous carbon is 1 to 20 μm, more preferably 5 to 10 μm.
[0014] The above method of the present application effectively improves the adsorption capacity of porous carbon channels for silicon source gas by modifying porous carbon. Specifically, porous carbon is mixed with zirconium ions, and ultrasonic dispersion is used to diffuse zirconium ions. Due to the high specific surface area and confinement effect of the channels, zirconium ions are mostly adsorbed in the channels, and then coordinated and assembled with organic ligands to form a MOF structure in the channels. The polar groups and coordinated unsaturated sites of the structure make it have excellent affinity for silicon source gas; on the other hand, the highly ordered porous structure of MOFs significantly increases the specific surface area of the channels, and further improves the adsorption capacity for silicon source gas. Therefore, the porous carbon modified as above does not change much in pore volume, but its adsorption capacity for silane gas is significantly enhanced, which effectively reduces the floating silicon content on the surface of the porous carbon and improves the cycle stability of the negative electrode material.
[0015] It is worth noting that the amount of zirconium salt added should be appropriate. If the amount of zirconium salt added is too high, it will have a significant impact on the pore volume of porous carbon and will not be conducive to increasing the silicon content after deposition. Otherwise, it will be difficult to form a stable MOF structure.
[0016] It should be noted that the MOF structure uses zirconium ions as coordination ions, has excellent high temperature resistance, and can withstand the high temperature of the silicon deposition process. The metal oxide formed by its high temperature pyrolysis can also improve the adsorption capacity of the pores to the silicon source gas. In addition, the coordination bond strength formed by the amino-containing polycarboxylic acid ligand is relatively high, and a three-dimensional network structure with an fcu topological structure can be formed, thereby improving the temperature resistance.
[0017] Preferably, the sphericity of the porous carbon matrix is greater than 0.8, more specifically 0.8 to 0.99.
[0018] It should be noted that the sphericity represents the ratio of the surface area of a sphere having the same volume as the particle to the surface area of the particle, wherein the sphericity of a perfectly spherical particle is 1. And the sphericity described in this application is the median sphericity or average sphericity of multiple particles. The higher the sphericity, the smaller the surface area of the porous carbon under the same volume, which is more conducive to improving the adsorption capacity of the pore structure for metal ions and silicon source gas.
[0019] Preferably, the activation treatment includes: in a first atmosphere, heating to 280-450°C at a rate of 1-5°C / min, and keeping the temperature for 1-3 hours; then heating to 700-900°C at a rate of 5-10°C / min, and keeping the temperature for 1-4 hours; obtaining an activated precursor; placing the activated precursor in a second atmosphere, and performing an oxidation treatment at 200-300°C for 1-2 hours, wherein the first atmosphere is an inert atmosphere, and the volume proportion of oxygen is 5-20%; the second atmosphere is a mixed atmosphere of nitrogen and oxygen.
[0020] Preferably, the carbon source precursor is petroleum coke or asphalt coke.
[0021] Preferably, the alkaline activator is sodium hydroxide and / or potassium hydroxide.
[0022] Preferably, the inert atmosphere is nitrogen or argon.
[0023] The above-mentioned activation treatment is firstly carried out with an alkaline activator to obtain an activated product with a porous structure by reacting the carbon material with an alkaline compound such as potassium hydroxide at a high temperature, and then low-temperature calcination is carried out under aerobic conditions. This is beneficial to the formation of abundant active sites such as carboxyl groups and hydroxyl groups in the product, especially in the pores with a large specific surface area, which helps to enhance its pre-coordination or adsorption capacity for metal ions and silicon source gases, thereby inhibiting the formation of floating silicon on the porous carbon surface.
[0024] In a second aspect, the present application provides a method for preparing a low expansion silicon-carbon negative electrode material, which comprises the following steps: The modified porous carbon is sent into a CVD deposition furnace, a protective atmosphere is introduced and the temperature is raised to 400-500°C, a silicon source gas is introduced to perform silicon deposition; and then a carbon source gas is introduced to perform carbon deposition; During the silicon deposition process, the silicon source gas flow rate is 0.05-0.1 L / min, the pressure in the furnace is 5-10 kPa, the temperature is 500-600° C., and the deposition time is 4-10 h; During the carbon deposition process, the carbon source gas flow rate is 0.1-5 L / min, the pressure in the furnace is 10-100 kPa, the temperature is 800-1000° C., and the deposition time is 3-6 hours.
[0025] Preferably, during the carbon deposition process, the pressure in the furnace is increased to the target pressure at a rate of 0.1-1 kPa / min.
[0026] Preferably, the silane gas is monosilane or disilane; and the carbon source gas is selected from one or more of methane, ethane, propane, acetylene, ethylene, styrene and propylene.
[0027] During the silicon deposition process, controlling the silicon source gas within a lower flow rate range and lower pressure conditions helps to control the silicon deposition rate, promotes the diffusion of the silicon source gas into the pores for deposition, and reduces floating silicon deposition on the carbon surface. In addition, the present application helps to obtain a carbon coating that is sparse inside and dense outside by controlling the uniform increase in the pressure in the furnace during the carbon deposition process. Specifically, the initial pressure in the furnace is low, which helps to obtain a loose carbon structure, and as the pressure increases, the density of the surface carbon structure increases. The carbon coating layer of this structure can not only meet the density requirements of the carbon coating layer to block the direct contact between the deposited silicon and the electrolyte, prevent the silicon-based material from excessively dissolving in the electrolyte or side reactions, and extend the battery life; it also helps to meet the requirements of rapid lithium ion transmission and improve the coulomb efficiency.
[0028] In summary, this application has the following beneficial effects: The present application forms a MOF structure with high affinity for silane gas and high specific surface area in the porous carbon pores through modification, effectively increasing the amount of silicon deposition in the pores and inhibiting the floating silicon deposition on the porous carbon surface, thereby reducing the expansion rate of the negative electrode during the charge and discharge process and improving the cycle stability of the battery. Furthermore, the present application controls the sphericity of the porous carbon and bakes it in an oxygen-containing atmosphere, which to a certain extent promotes the adsorption capacity of the porous carbon for silane gas.
[0029] In addition, the present application obtains a carbon coating layer that is "sparse inside and dense outside" by controlling the growth curve of the furnace pressure during the carbon deposition process, which not only realizes the protective effect of the carbon coating layer on the deposited silicon, but also meets the ion transmission efficiency requirements of the battery, achieving a balance between battery life and coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an electron microscope image of the modified porous carbon obtained in Preparation Example 1.
[0031] Figure 2 This is an electron microscope image of the silicon-carbon negative electrode material obtained in Example 1.
[0032] Figure 3 This is a comparison chart of the silicon-carbon negative electrode material of Example 1 before and after the electrical expansion test.
[0033] Figure 4 This is a comparison chart of the silicon-carbon negative electrode material of Example 1 before and after the electrical expansion test. DETAILED DESCRIPTION Preparation Example
[0034] Preparation Example 1, a modified porous carbon, the preparation steps are as follows: Weigh 1kg of petroleum coke (200 mesh) and mix with 2.2kg of potassium hydroxide to obtain a mixture, place it in a nitrogen atmosphere, heat it to 390℃ at a rate of 3℃ / min, and keep it warm for 2h; then heat it to 800℃ at a rate of 5℃ / min, and keep it warm for 3h to obtain an activated precursor. The activated precursor is neutralized with hydrochloric acid to a pH of 6.5-7.5, then washed with deionized water, dried at 150℃, and then transferred to a calcining furnace, oxidized at 260℃ for 1h in a mixed atmosphere of nitrogen and oxygen (oxygen 10vol%), cooled to room temperature, and ball milled to obtain a porous carbon matrix with a sphericity of 0.9 (average value).
[0035] Take 100g of porous carbon matrix and 3.4g (0.01mol) Zr(NO3)4, add them to 1L deionized water, ultrasonically disperse for 20min, then add 1L DMF solution of 0.015mol / L 2-aminoterephthalic acid for coordination assembly, stir and react for 20min, centrifuge to separate the porous carbon, wash and dry, and obtain a BET specific surface area of 1877m 2 / g of modified porous carbon.
[0036] Preparation Example 2, a modified porous carbon, the preparation steps are as follows: Weigh 1kg of petroleum coke (200 mesh) and mix with 1.6kg of potassium hydroxide to obtain a mixture, place it in a nitrogen atmosphere, heat it to 420℃ at a rate of 5℃ / min, and keep it warm for 1h; then heat it to 900℃ at a rate of 10℃ / min, and keep it warm for 3h to obtain an activated precursor. The activated precursor is neutralized with hydrochloric acid to a pH of 6.5-7.5, then washed with deionized water, dried at 150℃, and then transferred to a calcining furnace, oxidized at 280℃ for 1h in a mixed atmosphere of nitrogen and oxygen (oxygen 10vol%), cooled to room temperature, and ball milled to obtain a porous carbon matrix with a sphericity of 0.85 (average value).
[0037] Take 100g of porous carbon matrix and 1.7g (0.005mol) Zr(NO3)4, add them to 1L deionized water, ultrasonically disperse for 20min, then add 1L DMF solution of 0.01mol / L 2-aminoterephthalic acid for coordination assembly, stir and react for 10min, centrifuge to separate the porous carbon, wash and dry, and obtain a BET specific surface area of 1683m 2 / g of modified porous carbon.
[0038] Preparation Example 3, a modified porous carbon, the preparation steps are as follows: Weigh 1kg of pitch coke (300 mesh) and mix with 3kg of potassium hydroxide to obtain a mixture, place it in a nitrogen atmosphere, heat it to 300℃ at a rate of 3℃ / min, and keep it warm for 3h; then heat it to 800℃ at a rate of 10℃ / min, and keep it warm for 3h to obtain an activated precursor. The activated precursor is neutralized with hydrochloric acid to a pH of 6.5-7.5, then washed with deionized water, dried at 150℃, and then transferred to a calcining furnace, oxidized at 220℃ for 2h in a mixed atmosphere of nitrogen and oxygen (oxygen 15vol%), cooled to room temperature, and ball milled to obtain a porous carbon matrix with a sphericity of 0.9 (average value).
[0039] Take 100g of porous carbon matrix and 2.7g (0.008mol) Zr(NO3)4, add them to 1L deionized water, ultrasonically disperse for 20min, then add 1L of 0.01mol / L ethylenediaminetetraacetic acid aqueous solution for coordination assembly, react for 10min, centrifuge to separate the porous carbon, wash and dry, and obtain a BET specific surface area of 2052m 2 / g of modified porous carbon.
[0040] Preparation Example 4, a modified porous carbon, is different from Preparation Example 1 in that the sphericity of the porous carbon matrix is 0.7.
[0041] Preparation Example 5, a modified porous carbon, the preparation steps are as follows: Weigh 1 kg of petroleum coke and 2.8 kg of potassium hydroxide and mix them evenly to obtain a mixture, which is placed in a nitrogen atmosphere and heated to 390°C at a rate of 3°C / min and kept warm for 2 hours; then heat it to 800°C at a rate of 5°C / min and keep warm for 3 hours to obtain an activated precursor. The mixture is cooled to room temperature and ball milled to obtain a porous carbon matrix with a sphericity of 0.9 (average value).
[0042] Take 100g of porous carbon matrix and 3.4g (0.01mol) Zr(NO3)4, add them to 1L deionized water, ultrasonically disperse for 20min, then add 1L DMF solution of 0.04mol / L 2-aminoterephthalic acid for coordination assembly, stir and react for 20min, centrifuge to separate the porous carbon, wash and dry, and obtain a BET specific surface area of 1803m 2 / g of modified porous carbon.
[0043] Preparation Example 6, a porous carbon, the preparation steps are as follows: Weigh 1kg of petroleum coke and 2.8kg of potassium hydroxide and mix them evenly. The mixture is placed in a nitrogen atmosphere and heated to 390℃ at a rate of 3℃ / min and kept warm for 2h; then heated to 800℃ at a rate of 5℃ / min and kept warm for 3h to obtain an activated precursor. The activated precursor is placed in a mixed atmosphere of nitrogen and oxygen (oxygen 10vol%) and oxidized at 260℃ for 1h. It is cooled to room temperature and ball milled to obtain a sphericity of 0.9 (average value) and a BET specific surface area of 1752m 2 / g of porous carbon. Example
[0044] Example 1, a silicon-carbon negative electrode material is prepared by the following steps: The modified porous carbon of Preparation Example 1 was sent into a CVD deposition furnace, protective argon gas was introduced and the temperature was raised to 450°C, monosilane gas was introduced, the flow rate of monosilane gas was controlled to 0.05L / min, the pressure in the furnace was 8kPa, the reaction temperature was 530°C, and silicon deposition was carried out for 6 hours; then acetylene gas was introduced, the flow rate of acetylene gas was controlled to 2L / min, the pressure in the furnace was 60kPa, the reaction temperature was 900°C, and carbon deposition was carried out for 5 hours.
[0045] Embodiment 2, a silicon-carbon negative electrode material is prepared by the following steps: The modified porous carbon of Preparation Example 2 was sent into a CVD deposition furnace, an argon atmosphere was introduced and the temperature was raised to 450°C, monosilane gas was introduced, the flow rate of monosilane gas was controlled to 0.06L / min, the pressure in the furnace was 5kPa, the reaction temperature was 550°C, and silicon deposition was carried out for 8 hours; then acetylene gas was introduced, the flow rate of acetylene gas was controlled to 3L / min, the pressure in the furnace was 80kPa, the reaction temperature was 800°C, and carbon deposition was carried out for 4 hours.
[0046] Embodiment 3, a silicon-carbon negative electrode material is prepared by the following steps: The modified porous carbon of Preparation Example 3 was sent into a CVD deposition furnace, an argon atmosphere was introduced and the temperature was raised to 500°C, monosilane gas was introduced, the flow rate of monosilane gas was controlled to 0.1 L / min, the pressure in the furnace was 10 kPa, the reaction temperature was 520°C, and silicon deposition was carried out for 5 hours; then acetylene gas was introduced, the flow rate of acetylene gas was controlled to 2 L / min, the pressure in the furnace was 30 kPa, the reaction temperature was 900°C, and carbon deposition was carried out for 6 hours.
[0047] Example 4, a silicon-carbon negative electrode material, is different from Example 1 in that the modified porous carbon of Preparation Example 1 is replaced by the modified porous carbon of Preparation Example 4.
[0048] Example 5, a silicon-carbon negative electrode material, is different from Example 1 in that the modified porous carbon of Preparation Example 1 is replaced by the modified porous carbon of Preparation Example 5.
[0049] Embodiment 6, a silicon-carbon negative electrode material is prepared by the following steps: The modified porous carbon of Preparation Example 1 was sent into a CVD deposition furnace, protective argon gas was introduced and the temperature was raised to 450°C, monosilane gas was introduced, the flow rate of monosilane gas was controlled to 0.05L / min, the pressure in the furnace was 8kPa, the reaction temperature was 530°C, and silicon deposition was carried out for 6 hours; then acetylene gas was introduced, the flow rate of acetylene gas was controlled to 2L / min, the pressure in the furnace was controlled to increase to 60kPa at a rate of 0.5kPa, the reaction temperature was 900°C, and carbon deposition was carried out for 5 hours.
[0050] Embodiment 7, a silicon-carbon negative electrode material is prepared by the following steps: The modified porous carbon of Preparation Example 1 was sent into a CVD deposition furnace, protective argon gas was introduced and the temperature was raised to 450°C, monosilane gas was introduced, the flow rate of monosilane gas was controlled to 0.05L / min, the pressure in the furnace was 8kPa, the reaction temperature was 530°C, and silicon deposition was carried out for 6 hours; then acetylene gas was introduced, the flow rate of acetylene gas was controlled to 2L / min, the pressure in the furnace was controlled to increase to 100kPa at a rate of 1kPa, the reaction temperature was 900°C, and carbon deposition was carried out for 5 hours. Comparative Example
[0051] Comparative Example 1, a silicon-carbon negative electrode material, differs from Example 1 in that the porous carbon of Preparation Example 6 replaces the modified porous carbon of Preparation Example 1. Performance testing
[0052] 1. Button battery expansion test Test information: The positive electrode uses NCM positive electrode, cut into 14mm diameter; Negative electrode: The silicon-carbon negative electrode material of the embodiment is used as the negative electrode active material. 90g of silicon-carbon negative electrode material, 4.0g of SP, 0.2g of SCNTs, 2.0g of CMC, 3.0g of SBR and 230mL of solvent are stirred and mixed to prepare a negative electrode slurry. The slurry is coated on a copper foil, dried, cold pressed, and cut into negative electrode sheets with a diameter of 16mm.
[0053] Electrolyte: 1.0M LiPF6, EC:DEC=1:1, 5.0%FEC (Vol%); Diaphragm: PP diaphragm, 19mm diameter; Test equipment: RSS1400; Constant pressure mode: 5kg.
[0054] Charging and discharging process:
[0055] Calculate the change in the thickness of the negative electrode sheet before and after the charge and discharge test, and calculate the test results according to the following formula: Expansion rate (%) = (thickness after test - thickness before test) / thickness before test × 100%; 2. Silicon content test: Place the silicon-carbon negative electrode material sample in a 5mol / L hydrochloric acid solution, stir and soak for 6 hours to remove zirconium ions. Then filter the sample and wash it with deionized water until the pH is 6.5-7. After filtering and drying, place it in a corundum crucible, and place the crucible in a muffle furnace at 1200℃ for calcination for 10 hours to complete the combustion of carbon in the material and the oxidation of silicon; during the process, record the crucible weight m0, sample weight m1, and the total weight of the crucible and product after calcination m2, and calculate the silicon content according to the following formula: Si (%) = (m2-m0) / m1×28.09 / 60.09×100%.
[0056] 3. Electrical performance test Sample information: Positive electrode: NCM positive electrode, cut to 14mm diameter; Negative electrode: The silicon-carbon negative electrode material of the embodiment is used as the negative electrode active material, 90g of the silicon-carbon negative electrode material, 4.0g of SP, 0.2g of SCNTs, 2.0g of CMC, 3.0g of SBR and 230mL of solvent are stirred and mixed to prepare a negative electrode slurry, which is coated on a copper foil, dried, cold pressed, and cut into negative electrode sheets with a diameter of 16mm; Electrolyte: 1.0M LiPF6, EC:DEC=1:1, 5.0%FEC (Vol%); Diaphragm: PP diaphragm, 19mm diameter; 1) Discharge capacity in grams: The assembled button cell was tested on a battery testing system with a test voltage range of 0.005V-1.5V. The cell was allowed to stand for 30 minutes, discharged at a constant current of 0.1C to 0.01V, allowed to stand for 5 minutes, and then discharged at a constant current of 0.02C to 0.005V. The discharge capacity in grams was divided by the mass of the active substance (silicon-carbon material) to obtain the discharge capacity in grams of the silicon-carbon material.
[0057] 2) Cycle stability test: First charge and discharge capacity: Use a battery tester (RSS1400) to perform the first charge and discharge, charge to 4.2V, then discharge to 3.0V, and record the initial discharge capacity.
[0058] The battery tester (RSS1400) was set up for cycle testing, using the constant current charge and discharge mode. The battery was charged to 4.2V at 0.1C, and then discharged to 3.0V at 0.1C for 300 cycles. The discharge capacity was recorded, and the discharge capacity retention rate after 300 cycles was calculated.
[0059] 4. Conductivity test: Use a powder conductivity meter (model RK02-FT-8100A) based on the four-probe test principle and in accordance with GB / T 1552-1995 to measure the conductivity of the silicon-carbon negative electrode material online by compressing the volume to a set pressure value or pressure under hydraulic power.
[0060] Table 1. Performance test results
[0061] It can be seen from Table 1 that, compared with the comparative example, the embodiment of the present application, through modification, assembling the MOF structure in the porous carbon pores, can effectively reduce the expansion of the negative electrode during the charge and discharge cycle and improve the cycle stability.
[0062] In addition, compared with other embodiments, embodiments 6 to 7 of the present application can improve the ion transport performance and enhance the electrical conductivity while maintaining the cycle performance by controlling the growth curve of the reaction pressure during the carbon deposition process.
[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A low expansion silicon-carbon negative electrode material, characterized in that: The method comprises modified porous carbon, nano-silicon deposited in the pores of the porous carbon and a carbon coating layer located on the surface of the porous carbon; the porous carbon is prepared according to the following steps: The carbon source precursor is mixed with an alkaline activator and activated to obtain a porous carbon matrix; The porous carbon matrix and the zirconium salt are added into deionized water, ultrasonically dispersed, and then an organic ligand is added for coordination assembly to obtain a modified porous carbon; The mass ratio of the porous carbon matrix to the zirconium salt is 100:1.6-3.
8.
2. The material according to claim 1, characterized in that The carbon source precursor is petroleum coke or asphalt coke.
3. The material according to claim 1, characterized in that The sphericity of the porous carbon matrix is greater than 0.
8.
4. The material according to claim 1, characterized in that The organic ligand is a polycarboxylic acid ligand containing an amino group.
5. The material according to claim 4, characterized in that The amino-containing polycarboxylic acid ligand is 2-aminoterephthalic acid or ethylenediaminetetraacetic acid.
6. The material according to claim 1, characterized in that The molar ratio of the organic ligand to the zirconium ion is 1:1.5-2.
7. The material according to claim 1, characterized in that The activation treatment comprises: in a first atmosphere, heating to 280-450°C at a rate of 1-5°C / min, and heat preservation for 1-3 hours; then heating to 700-900°C at a rate of 5-10°C / min, and heat preservation for 1-4 hours; obtaining an activated precursor; placing the activated precursor in a second atmosphere, and performing an oxidation treatment at 200-300°C for 1-2 hours, wherein the first atmosphere is an inert atmosphere, and the volume proportion of oxygen is 5-20%; and the second atmosphere is a mixed atmosphere of nitrogen and oxygen.
8. A method for preparing a low expansion silicon-carbon negative electrode material, characterized in that: The steps include: The modified porous carbon is sent into a CVD deposition furnace, a protective atmosphere is introduced and the temperature is raised to 400-500°C, a silicon source gas is introduced to perform silicon deposition; and then a carbon source gas is introduced to perform carbon deposition; During the silicon deposition process, the silicon source gas flow rate is 0.05-0.1 L / min, the pressure in the furnace is 5-10 kPa, the temperature is 500-600° C., and the deposition time is 4-10 h; During the carbon deposition process, the carbon source gas flow rate is 0.1-5 L / min, the pressure in the furnace is 10-100 kPa, the temperature is 800-1000° C., and the deposition time is 3-6 hours.
9. The method according to claim 8, characterized in that During the carbon deposition process, the pressure in the furnace is increased to the target pressure at a rate of 0.1-1 kPa / min.
10. The method according to claim 8, characterized in that The silane gas is monosilane or disilane; the carbon source gas is selected from one or more of methane, ethane, propane, acetylene, ethylene, styrene and propylene.
Citation Information
Patent Citations
Porous carbon and preparation method thereof, silicon-carbon negative electrode material and preparation method of silicon-carbon negative electrode material
CN117776183A